2008
DOI: 10.1103/physrevd.77.062002
|View full text |Cite
|
Sign up to set email alerts
|

Search for gravitational waves from binary inspirals in S3 and S4 LIGO data

Abstract: We report on a search for gravitational waves from the coalescence of compact binaries during the third and fourth LIGO science runs. The search focused on gravitational waves generated during the inspiral phase of the binary evolution. In our analysis, we considered three categories of compact binary systems, ordered by mass: (i) primordial black hole binaries with masses in the range 0.35M center dot m(1), m(2) 1.0M center dot, (ii) binary neutron stars with masses in the range 1.0M center dot m(1), m(2) 3.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
127
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 48 publications
0
127
0
Order By: Relevance
“…The standard template for the LSC-Virgo search [5][6][7][8]10] is based on the non-spinning post-Newtonian inspiral waveforms, calculated directly in the Fourier domain through the stationary phase approximation [85,91]. These waveforms, referred to as SPA or TaylorF2, are parameterized by the binary's component masses m 1 and m 2 [92][93][94], or equivalently by total mass M = m 1 + m 2 and symmetric mass ratio η = m 1 m 2 /M 2 .…”
Section: Inspiral Only Waveforms From the Post-newtonian Expansionmentioning
confidence: 99%
“…The standard template for the LSC-Virgo search [5][6][7][8]10] is based on the non-spinning post-Newtonian inspiral waveforms, calculated directly in the Fourier domain through the stationary phase approximation [85,91]. These waveforms, referred to as SPA or TaylorF2, are parameterized by the binary's component masses m 1 and m 2 [92][93][94], or equivalently by total mass M = m 1 + m 2 and symmetric mass ratio η = m 1 m 2 /M 2 .…”
Section: Inspiral Only Waveforms From the Post-newtonian Expansionmentioning
confidence: 99%
“…This is followed by recognizing triggers that are coincident in multiple detectors and then computing network-based statistics for them that reveal their significance as GW candidates. (These hierarchical steps were introduced in [14] and have been used in multiple CBC searches ever since.) The final stage is used to compute the coherent network statistics for these coincident triggers.…”
Section: Introductionmentioning
confidence: 99%
“…Past experiments with multi-detector searches for GW signals from CBCs have shown that the statistics that are optimal in Gaussian and stationary noise (OGSN) cease to be so in real data, in general [14][15][16]. Instead a function of the chi-square-weighted [17] matched-filter [18] outputs has been found to deliver a better performance [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of searches for gravitational waves from various sources have already been conducted with data from LIGO and its international partners, see e.g., [6,7,8,9,10,11]. Data from LIGO, GEO600 and Virgo from S5 (and Virgo's corresponding run, VSR1) is currently being analyzed jointly by the LIGO Scientific Collaboration (which includes the GEO Collaboration) and the Virgo Collaboration.…”
mentioning
confidence: 99%